The Neglected Creatures of Forests: Wild Bees - Yasemin Güler (Doğal Afetler ve Çevre Dergisi)
Although honey bee (Apis mellifera L.) is the best known as pollinator and most common species in ecosystems, there are approximately 16.000 bee species all over the world that have been described so far. The importance of the presence of bees in all ecosystems, including forests, will be more clearly understood when approximately 80% of flowering plants are thought to be pollinated by animals. There is anthropogenic pressure on many temperate forest ecosystems. This pressure, which is directly or indirectly applied to the forests, such as the conversion of forest areas into agricultural areas, forest fires and interventions to water resources, leads to deterioration of plant associations and therefore to changes in forest fauna elements. Considering the habitat needs of wild bees in their efforts to improve forest areas that are damaged due to the mutualistic relationship between crops and bees, will help the ecosystem to recover more quickly. Because while many forest tree in temperate climates can be pollinated by wind, some of the broad leaved trees, shrubs, small tree species and many herbaceous flowering plants in the same areas need bees for pollination. These include Castanea sativa Mill. (Anatolian chestnut), Tilia spp. (Linden), Acer spp. (Maple species), Liquidambar orientalis Mill. (Sweetgum), Arbutus anrdache L. (Sandalwood), Cerasus mahalep (L.) Miller (Mahalep), Rhus coriaria L. (Sumac), Laurus nobilis L. (Laurel), Buxus sempervirens L. (Boxwood), Arbutus unedo L. (Strawberry tree), Cotinus coggygria Scop. (Smoke tree), Tamarix germanica L. (Tamariks), Sorbus aucuparia L. (Rowan tree), Erica arborea L. (Tree heath), Cercis siliquastrum L. (Redbud), Lavandula spp. (Lavender), Astragalus spp. (Tragacanth) and Althaea offinalis L. (Marshmallow). The protection and preservation of these plant species, which means the area of food and protection for wildlife, is also important for the prevention of erosion. Better refurbishment of the trees in a degraded forest and the maintaining of pollination, which will ensure the preservation of the biological diversity of the forest, depends on the existence of adequate number and variety of bee species in that forest. For this reason, both the protection of high density and species diversity is necessary for the sustainability of pollination services. It is only possible with the establishment of interconnected semi-natural areas suitable for wild bees and the protection of natural areas.